The Improvement of Teachers' Professional Competency in Learning through Principal's Management in SMP Negeri 3 Terentang - Sutrisno Sutrisno (STKIP Singkawang, 2021)
Principal management greatly affects the professional competence of teachers. In this case, the management of the principal is an effort that is based on moving, directing, and maintaining a person's behavior so that he is motivated to act to do something to achieve certain results or goals. In the concept of management related to organizational life, the management ability of the principal is very important in moving teachers to be more professional, because the principal has a broad influence in the world of education. The purpose of this school action research is to determine the extent to which principal coaching through principal management can improve professional competence. The instrument used in this study was observation. Data were analyzed using descriptive percentages. In this school action research was carried out in 2 cycles, from the results of the actions taken it was proven to increase the professional competence of teachers in learning, namely from 62.81% in cycle 1 to 80.76% in cycle 2. In other words, principal management carried out by researchers as school principals can improve teacher professional competence in learning.